Active dielectric metasurface based on phase‐change medium. Issue 6 (12th October 2016) - Chu, Cheng Hung; Tseng, Ming Lun; Chen, Jie; Wu, Pin Chieh; Chen, Yi‐Hao; Wang, Hsiang‐Chu; Chen, Ting‐Yu; Hsieh, Wen Ting; Wu, Hui Jun; Sun, Greg; Tsai, Din Ping
Abstract : The all‐dielectric reconfigurable metasurfaces based on switchable phase‐change material Ge2 Sb2 Te5 with functional diversity for light modulation are shown. The tunability of EIT resonance on phase‐change metamolecule and the steering of gradient metasurface are demonstrated by selectively modifying the phase of selected constituent Ge2 Sb2 Te5 rods. Abstract: We propose all‐dielectric metasurfaces that can be actively re‐configured using the phase‐change material Ge2 Sb2 Te5 (GST) alloy. With selectively controlled phase transitions on the composing GST elements, metasurfaces can be tailored to exhibit varied functionalities. Using phase‐change GST rod as the basic building block, we have modelled metamolecules with tunable optical response when phase change occurs on select constituent GST rods. Tunable gradient metasurfaces can be realized with variable supercell period consisting of different patterns of the GST rods in their amorphous and crystalline states. Simulation results indicate a range of functions can be delivered, including multilevel signal modulating, near‐field coupling of GST rods, and anomalous reflection angle controlling. This work opens up a new space in exploring active meta‐devices with broader applications that cannot be achieved in their passive counterparts with permanent properties once fabricated.